Half a century of suicide studies - a plea for new directions in research and prevention - Maniam, T; Chan, L.F. (Universiti Kebangsaan Malaysia, 2013)
Suicide studies in Malaysia tend to be repetitive. Data from hospital studies, small scale community surveys and national epidemiological studies over nearly 50 years have consistently shown that there are real ethnic differences in terms of suicides and attempted suicides in this country, though some of these differences appear to be narrowing somewhat. Malays have shown significantly lower rates of suicidal ideas, attempts and completed suicides. Indians, on the other hand, figure prominently at the other end with high rates in all the above parameters. The reasons for these are also necessarily complex. Experience elsewhere from studies of the Indian diaspora have elucidated a number of explanations, which include the effects of poverty, acculturation, alcoholism, the lack of a strong religious protective factor as well as increased rates of mental ill-health. Efforts to contain this public health problem have been somewhat patchy. This has largely depended on efforts by non-government organizations such as the Befrienders whereas the public response lags behind in providing the financial and other resources necessary for a comprehensive national program. This paper reviews the relevant literature and suggest new areas for research as well as steps to provide a fresh impetus to suicide prevention in Malaysia.